1996
DOI: 10.1128/jb.178.7.2086-2093.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the stable maintenance properties of the par region of broad-host-range plasmid RK2

Abstract: A 3.2-kb fragment encoding five genes, parCBA/DE, in two divergently transcribed operons promotes stable maintenance of the replicon of the broad-host-range plasmid RK2 in a vector-independent manner in Escherichia coli. The parDE operon has been shown to contribute to stabilization through the postsegregational killing of plasmid-free daughter cells, while the parCBA operon encodes a resolvase, ParA, that mediates the resolution of plasmid multimers through site-specific recombination. To date, evidence indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 50 publications
1
49
0
2
Order By: Relevance
“…Previous work has demonstrated that the 0.7-kb region, a segment of the 3.2-kb region which encodes the entire parDE operon, stabilizes plasmids via a growth inhibition or cellkilling mechanism (38,46). These results suggested that ParE is a toxin, while ParD is an antitoxin protein that neutralizes the activity of ParE.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous work has demonstrated that the 0.7-kb region, a segment of the 3.2-kb region which encodes the entire parDE operon, stabilizes plasmids via a growth inhibition or cellkilling mechanism (38,46). These results suggested that ParE is a toxin, while ParD is an antitoxin protein that neutralizes the activity of ParE.…”
Section: Discussionmentioning
confidence: 51%
“…These studies further indicated that ParD and ParE are proteins of a toxin-antitoxin system analogous to those found on plasmids F and R1, with ParE acting as the toxic component. Stabilization of plasmids in E. coli by the parDE operon has been shown to be accompanied by growth inhibition and filamentation of plasmid-free segregants (38,46). In addition, plasmids carrying the parDE operon can be destabilized by providing ParD in trans from a compatible plasmid that is maintained by antibiotic selection (38).…”
mentioning
confidence: 99%
“…The res site is found within a 100-bp region between the two promoters P parCBA and P parDE . Earlier work using mini-RK2 replicons indicated that multimer resolution activity specified by the parCBA operon by itself does not account for the level of stabilization observed (29,31,35). ParB has been shown to be…”
mentioning
confidence: 99%
“…ParB has been shown to be an endonuclease, but its contribution to the stable maintenance provided by the parCBA operon is not known. It has been proposed that the ParA, ParB, and ParC proteins make up an active partition complex (8,29,31,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation